2018
DOI: 10.1177/1049732318788377
|View full text |Cite
|
Sign up to set email alerts
|

Men’s and Women’s Approaches to Disclosure About BRCA-Related Cancer Risks and Family Planning Decision-Making

Abstract: Little is known about how men and women who test positive for a BRCA gene mutation or have a strong family history of carrying a BRCA mutation manage disclosures about their BRCA-related cancer risks and family planning decision-making. By conducting interviews with 25 men and 20 women, this study investigated men's and women's approaches to disclosing their BRCA-related cancer risks and family planning decision-making. Guided by the Disclosure Decision-Making Model (DD-MM), this study demonstrates that men an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Additionally, the results showed that rejection of carrier partners was associated with a negative attitude toward genetic testing and disclosure of genetic test results, which was comparable with the attitudes observed in previous studies. This suggests the importance of communicating health concerns related to BRCA1/2 mutations and their consequences not only to carriers but also to healthy populations [ 5 11 13 14 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the results showed that rejection of carrier partners was associated with a negative attitude toward genetic testing and disclosure of genetic test results, which was comparable with the attitudes observed in previous studies. This suggests the importance of communicating health concerns related to BRCA1/2 mutations and their consequences not only to carriers but also to healthy populations [ 5 11 13 14 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The grounded theory approach was used to code, summarize, and condense the data. This approach is wellsuited for the analysis of the interview data because it is conducive to understanding how a process works (Creswell, 2006). This approach was applied to understand how physicians access psychosocial information in the course of the primary care visit.…”
Section: Discussionmentioning
confidence: 99%
“…After identifying broad themes, each coder independently conducted an analysis using grounded descriptive coding techniques ( Morgan and Nica, 2020 , Braun and Clarke, 2006 , Braun and Clarke, 2019 ). This ground-up approach utilized an ongoing process in which initial insights influence the direction of subsequent questions and interview topics ( Ormondroyd et al, 2012 , Dean and Rauscher, 2018 ). Across several meetings, results were compared and thoroughly discussed for consistency with the goal of identifying the overarching (major) themes and subthemes.…”
Section: Methodsmentioning
confidence: 99%
“…A paucity of research has found that genetic mutations alter the dynamic of family systems and relationships. As outlined in past qualitative research, the nature of BRCA1 / 2 genetic mutations often suggests an impending cancer diagnosis at some point in one’s life ( Dean, 2016 , Hesse-Biber, 2018 ), which in turn can negatively impact solidarity of family relationships and communicative patterns ( Dean et al, 2017 , Dean and Rauscher, 2018 ). While genetic testing/counseling is growing in popularity and accessibility, past literature has overlooked the impact, both negative and positive, that genetic testing/counseling may have on women at risk for these mutations.…”
Section: Introductionmentioning
confidence: 99%